Integrated geological-geophysical investigation of gold-hosting Rhyacian intrusions (Yaou, French Guiana), from deposit-to district-scale. (March 2022) - Combes, Vincent; Eglinger, Aurélien; André-Mayer, Anne-Sylvie; Teitler, Yoram; Jessell, Mark; Zeh, Armin; Reisberg, Laurie; Heuret, Arnauld; Gibert, Pierre
Abstract: The mineral system concept, which combines integrated information from all kinds of geological and geophysical studies, is a very useful approach to predict and locate structures and lithologies potentially associated with gold mineralization at all scales (i.e., upscaling from craton-to district-to camp-to deposit-scale). This is demonstrated in this study where the Yaou deposit, located in French Guiana within Rhyacian terranes, formed and deformed during the Trans-Amazonian orogenic cycle (ca. 2600-1950 Ma), is used as a case study. The deposit comprises numerous intrusions hosting the bulk of the high-grade gold mineralization at Yaou, associated with a quartz-carbonate veining system. Both intrusive and gold events are dated in order to constrain Yaou in the regional litho-structural framework. Spatially associated with the Central Yaou Shear Zone (CYSZ), one of the quartz monzodiorite yields a U–Pb zircon age of 2131 ± 6 Ma, supra-chondritic εHft of ca. 2.5, and Hf model ages at ca. 2.6–2.4 Ga. These data suggest Paleoproterozoic rock formation due to reworking of juvenile crust, derived from the depleted mantle during the late Archean to early Paleoproterozoic. The main and economic gold event hosted by the quartz monzodiorite is dated at 2105 ± 25 Ma by Re–Os isotope analyses of Au-bearing pyrite, representing the first date for gold mineralization in French Guiana. A multi-scale approach using airborne magnetic and radiometric data allows to better understand the spatial distribution of the intrusions and possibly associated shear zones, both related to gold mineralization events. The intrusions and associated shear zones are interpreted as being parallel along a N60° trend and replicated laterally toward the northwest. A temporal association is defined between the shearing deformation and the magmatic event, both being synchronous with a possibility of pre-shearing intrusion and a protracted magmatic phase active while shearing. The Yaou-type intrusion-hosted mineralization can be targeted along these N60°-striking structures. This integrated approach opens some targeting options, previously unrecognized within the southern Paramaca Greenstone Belt. Highlights: A coupled geological-geophysical approach is proposed. The Yaou gold deposit (French Guiana) is used as a case study. Intrusions hosting the bulk of the gold mineralization, dated at 2131 ± 6 Ma (U–Pb on zircon). The main and economic gold event is dated at 2105 ± 25 Ma (Re–Os on Au-bearing pyrite).